RESPON KEBIJAKAN PEMERINTAH DESA TERHADAP PERATURAN BUPATI WAJIB MADRASAH DINIYAH - Kuswandi, Iwan; Wajdi, Muh Barid Barid Nizarudin; Al Faruq, Umar; Zulhijra, Zulhijra; Khairudin, Khairudin; Khoiriyah, Khoiriyah (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2020)
This paper discusses the study about village government policy towards regional head regulation regarding the obligations of the madrasa diniyah program. The results of this study, madrasah diniyah is community based education, from, by and for the community.In life with the community, government officials in the village, they live with the community. They know and understand the problems of the madrasahdiniyah in their village. Existing reality,government officials in the village cannot carelessly channel aid from the village fund program from the government, because in its rules, it does not explicitly mention assistance for madrasahdiniyah, instead it is available for early childhood education.There is a regulation from the regional head regarding the mandatory madrasah diniyah program,then there is BOSDA funding, however backfired for madrasahdiniyah education, their number increased from the number before the regulation.